Pengaruh Perceived Quality, Aesthetics dan Conformance Terhadap Keputusan Pembelian Shopeefood Chatime Kediri - Angga Rizka Lidiawan; Nur Laely (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2022)
The purpose of this study is to find out the partial and simultaneous influence on perceived quality, aesthetics and conformance aspects on purchasing decisions in Shopee Food E-Commerce Chatime Kediri. The participation of respondents was 200 people with purposive random sampling methods. Statistical methods use multiple linear regression, partial test, and simultant test. Each aspect of research uses each of the 3 indicators as a step to know the dominating role. The results of this study showed that the conformance (X3) aspect with X31 code is very dominant from the descriptive side. The results of this study stated that the partial influence of Perceived Quality amounted to -3,248, Aesthetics by 3,006, and Conformance by 7,006, while simultaneously amounted to 28,896. The dominating aspect is Conformance, because it plays a big role in the Purchase Decision in Shopee Food E-Commerce Chatime Kediri.